2014
DOI: 10.1007/s10815-014-0208-1
|View full text |Cite|
|
Sign up to set email alerts
|

Sequential (hFSH + recFSH) vs homogenous (hFSH or recFSH alone) stimulation: clinical and biochemical (cumulus cell gene expression) aspects

Abstract: FSH is a key hormone in the regulation of follicular development. Together with the EGF network, these molecules mediate oocyte maturation and competence in preparation for the action of LH. FSH isoforms regulate distinct biological pathways and have specific effects on granulosa cell function and maturation of the ovarian follicle. Their dynamic interactions occur during the follicular cycle; shortliving forms are predominant in the pre-ovulatory phase, whereas long-acting molecules characterize the lutealfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The assay and a result using this highly pure pituitary FSH are shown in previous work . The physiological FSH has a longer half‐life, includes more isoforms, and is physiologically glycosylated . Since response to isoforms might vary, and the physiological hormone works best with the novel low‐level receptor, we used the Fitzgerald highly pure FSH (specific activity >5000 IU/mg) in subsequent work.…”
Section: Methodsmentioning
confidence: 99%
“…The assay and a result using this highly pure pituitary FSH are shown in previous work . The physiological FSH has a longer half‐life, includes more isoforms, and is physiologically glycosylated . Since response to isoforms might vary, and the physiological hormone works best with the novel low‐level receptor, we used the Fitzgerald highly pure FSH (specific activity >5000 IU/mg) in subsequent work.…”
Section: Methodsmentioning
confidence: 99%
“…When examining the different commercial FSH preparations, the isoforms present in uFSH are more acidic than those in rFSH [ 18 ]. Interestingly, based on the natural distribution of FSH isoforms during the follicular phase of the menstrual cycle, Gurgan et al [ 19 ] have demonstrated favorable outcomes and improved efficacy, while using a sequential administration of uFSH followed by rFSH compared with either FSH preparation alone. Moreover, when prospectively evaluating the efficacy of a protocol that mimics the physiological shift form an acidic to a less acid FSH isoform during oocyte maturation, Gerli and Di Renzo [ 20 ] could demonstrate that the combined protocol (hFSH + rFSH) resulted in significantly less IU of FSH necessary for ovarian stimulation together with shorter stimulation days and with higher number of oocyte yield, embryo quality, implantation and pregnancy rates.…”
Section: Fsh Preparationsmentioning
confidence: 99%
“…Gurgan et al [ 72 ], aiming to identify markers capable of predicting the quality of human oocytes detected the presence of the RCHY1 gene as a possible hormone regulator involved in follicular development, further emphasizing that this gene is close (383 kb) to the conception rate and daughter pregnancy rate QTL.…”
Section: Discussionmentioning
confidence: 99%